Tinjauan Hukum Praktik Komersialisasi Lagu dan/atau Musik Melalui Non-Fungible Token (NFT) Oleh Para Musisi di Indonesia - Muhammad Rifqi Hariri; Ahmad M. Ramli; Tasya Safiranita Ramli (Publikasi Indonesia, 2023)
This study analyzes the potential benefits and legal issues that arise, especially in the field of intellectual property due to the practice of commercializing songs and/or music through NFTs by musicians in Indonesia. Through descriptive analytical research using a normative juridical approach, the results of this study indicate that there are various potential benefits that can be obtained by musicians and the public as NFT buyers if works in the form of songs and/or music are commercialized through NFT. However, aside from that, there are also potential problems, such as the current absence of regulations in Indonesia that specifically regulate NFTs, which causes legal uncertainty. Indonesia needs to issue regulations that specifically regulate the legality of NFTs through a multidisciplinary approach, especially from the technological and legal aspects.